Perception of Language Learning Strategies Used by Indonesian Secondary School Learners According to Gender and Field of Study and Their Relationships With English Language Achievement - Syamsuar, Khairul (2004)
This study aims to examine the kinds of strategies used by Indonesian secondary school students in learning English as a foreign language, and to determine how their use varies according to gender and field of study. It also aims to study the relationships between the use of language learning strategies and English language achievement and to determine which category of strategies is more predictive of English language achievement. Three hundred students were selected as sample using proportional stratified random sampling. Data were gathered using a questionnaire to collect data on the use of language learning strategies, and achievement test to collect data on English language achievement. Data were analyzed using ANOVA and Chi-square to determine the variation in the use of language learning strategies. Pearson coefficient correlation was used to study the relationships between the use of language learning strategies and English language achievement, and a stepwise multiple-regression model was used to determine which category of strategies is more predictive of English language achievement. This study found that the use of language learning strategies by Indonesian secondary school students can be categorized or considered as a moderate use, indicated with overall mean score (3.0), the range of the mean scores of the six categories of strategies (from 2.8 to 3.4), and the percentage of individual strategies that were used at middle level of use (62%). Another finding of this study was that the use of language learning strategies significantly varied by gender and field of study. Female students used language learning strategies significantly more often than males students, and students who majored in exact science used language learning strategies significantly more often than those who majored in social science. It was also found that the use of overall strategies and the six categories of strategies except affective strategies and English language achievement were correlated significantly. Of the six categories of strategies, only compensation, affective and cognitive strategies provide a positive and significant contribution for the total variation in English language achievement. These three categories of strategies jointly accounted for 28 percent of the grade variability in English language achievement